Effects of Eccentric Phase Velocity on Bench Press Concentric Bar Velocity in the Young and Elderly - Calandrini, Antenor; Penna, Eduardo Macedo; Monteiro, Elren Passos; Boullosa, Daniel; Coswig, Victor Silveira (International Journal of Sports Medicine, 2024)
This study aimed to investigate the impact of bar velocity during the eccentric phase on subsequent concentric performance in the young and elderly. Twelve elderly women (65.2+4.2 years) and 16 young women (23.1+2.1 years) were randomly assigned to four experimental conditions that combined high-velocity eccentric actions (HVECC; maximum velocity) and moderate-velocity eccentric actions (MVECC; 2.0 s), using 30% and 60% of their 1-repetition maximum (1RM) on the Smith machine bench press. Measurements of mean propulsive velocity (MPV), peak velocity (PV), and mean power (MP) were recorded. Two-way ANOVA with repeated measures was applied for each variable, when needed, the Bonferroni post hoc was used. Statistical significance was set at p<0.05, and effect size (ES) was established by Cohen’s dz. The results demonstrated that elderly women showed improved performance in MPV (+10.0%; ES=− 0.58; p=0.009) and MP (+11.7%; ES=− 0.14; p=0.045) when utilizing HVECC at 30% 1RM only. Moreover, young women exhibited superior performance for both 30% and 60% 1RM when using HVECC for all variables analyzed (p<0.05). The HVECC appears to have an impact on the subsequent performance of the concentric phase, particularly when lighter loads (30% 1RM) are utilized, regardless of the age group.
Keywords: resistance training; elderly; exercise; muscle strength